2023
DOI: 10.3389/fmicb.2023.1227147
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of novel bacteriophage vB_KpP_HS106 for Klebsiella pneumonia K2 and applications in foods

Changrong Chen,
Zhenxiang Tao,
Tengteng Li
et al.

Abstract: The detection rate of Klebsiella pneumoniae in food is increasing, and it has emerged as a food pathogen. Global health is threatened due to the emergence of multidrug-resistant (MDR) and hypervirulent (hv) K. pneumoniae. Phages have a promising application as antibacterial agents and have the ability to lyse MDR strains. Hence, phage vB_KpP_HS106 against MDR-hv K. pneumoniae strains was isolated from sewage collected from a hospital. It can maintain stable activity at a pH range of 4–12 and a temperature rang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…Similar results have been obtained with phage K2a [42]. However, in general, the adsorption rate of phage KP1LMA is lower than in other studies for Klebsiella phages [24,42,43]. Phage LASTA and SJM3 adsorption assays showed that approximately 97 and 94%, respectively, of the phage particles were adsorbed to K. pneumoniae after 20 min [24].…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…Similar results have been obtained with phage K2a [42]. However, in general, the adsorption rate of phage KP1LMA is lower than in other studies for Klebsiella phages [24,42,43]. Phage LASTA and SJM3 adsorption assays showed that approximately 97 and 94%, respectively, of the phage particles were adsorbed to K. pneumoniae after 20 min [24].…”
Section: Discussionsupporting
confidence: 84%
“…Phages LASTA and SJM3 presented a higher burst size of 187 ± 37 and 155 ± 34 PFU/host cell, respectively, and a long latent period of 80 min [24]. In another study, phage HS106 presented higher burst size (183 PFU/host cell) and low latent period (10 min) [43]. However, the phage's burst size is also affected by the host, as observed by Kondo (2023) [49].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations